Westward advancement of Pseudonereis anomala (Polychaeta: Nereididae) in the Mediterranean Basin (Piraeus, Saronikos Bay, Aegean Sea) - KAMBOUROGLOU, V.; NICOLAIDOU, A. (Mediterranean Marine Science, 2006)
This paper reports the establishment of the Lessepsian Pseudonereis anomala (Gravier, 1901) in its new locality in the port of Piraeus (Saronikos Bay) and provides additional information on its population. The mean densities of P. anomala ranged from 0 indiv./m2 to 382.5 indiv./m2 among the calcareous alga Corallina elongata. A variety of sizes (length of the head and fi rst ten chaetigerous segments) was observed ranging fromPseudonereis anomala; Saronikos Gulf; Polychaete; Immigrant. 1.3mm to 8.1mm. There are indications that P. anomala may compete with other species of Nereididae. Accepted in December 2006